Midbrain area and the hummingbird sign from brain MRI in progressive supranuclear palsy and idiopathic normal pressure hydrocephalus. Issue 1 (14th September 2021) - Virhammar, Johan; Blohmé, Harald; Nyholm, Dag; Georgiopoulos, Charalampos; Fällmar, David
ABSTRACT: Background and Purpose: The main radiological finding in progressive supranuclear palsy (PSP) is reduced midbrain volume. Both qualitative (e.g., hummingbird sign) and quantitative (e.g., area measurements) markers have been noted. Recent studies have shown a similar reduction also in idiopathic normal pressure hydrocephalus (iNPH). The purpose was to investigate the reliability and accuracy of these markers in discriminating PSP from iNPH and controls. Methods: Eight neuroradiologists viewed sagittal MR images of the midbrain from 104 subjects: 26 PSP patients, 40 iNPH patients, and 38 healthy controls. They visually assessed whether the hummingbird sign was present or not, grading their confidence from 1 to 5. Assessments were translated into a score between +5 and –5: from maximum confidence of presence to maximum confidence of absence. A positive median score was considered to indicate hummingbird sign. Sagittal midbrain area was manually measured in each subject. Results: Seventy‐seven percent of PSP patients, 65% of iNPH, and 3% of controls were visually assessed as having the hummingbird sign. Manually measured midbrain area also showed overlap between PSP and iNPH. Regarding discrimination of PSP patients, midbrain area measurements, using a cutoff of 90 mm 2, yielded a higher area under the curve (AUC = 0.86) than visual assessment scores (AUC = 0.83), and higher reliability. Conclusions: Measuring sagittal midbrain area is more accurate and reliable than visual assessment. Due to significant overlap in appearance, a midbrain with a hummingbird sign or reduced sagittal area should raise the suspicion of PSP only after other signs of iNPH have been considered.